Analysis of the Quality of Package Delivery Services in the Decision to Use Postal Services - Nurhaliza, Aida; Zaini, Oktori Kiswati; Wihartika, Doni (INOVATOR, 2024)
The purpose of this research are find out the service quality at PT. Pos Indonesia Cibinong and the decision customers to use package delivery services at PT. Pos Indonesia Cibinong. The kind of research used is exploratory descriptive. This study uses qualitative primary data and quantitative secondary data. The Determination of the sampling method of sample uses the method accidential. The method of analysis that used descriptive analysis that is data using application SPSS 22. Furthermore, using tabulation analysis. The result show that the service quality at PT. Pos Indonesia Cibinong already good, but for reliability of package delivery it is still not good because it produces 70.20% and it’s so small when compared to other statements, and then customers decide to use package delivery services at PT. Pos Indonesia Cibinong because of the distributors regarding the location and ease of accessing package information.